Acute Depletion of D2 Receptors from the Rat Substantia Nigra Alters Dopamine Kinetics in the Dorsal Striatum and Drug Responsivity - Budygin, Evgeny A.; Oleson, Erik B.; Lee, Yun Beom; Blume, Lawrence C.; Bruno, Michael J.; Howlett, Allyn C.; Thompson, Alexis C.; Bass, Caroline E. (Frontiers in Behavioral Neuroscience, 2017)
Recent studies have used conditional knockout mice to selectively delete the D2 autoreceptor; however, these approaches result in global deletion of D2 autoreceptors early in development. The present study takes a different approach using RNA interference to knockdown the expression of the D2 receptors in the SN, including dopaminergic neurons, which project primarily to the dorsal striatum in adult rats. This approach restricts the knockdown primarily to nigrostriatal pathways, leaving mesolimbic D2 autoreceptors intact. Analyses of dopamine kinetics in the dorsal striatum reveal a decrease in dopamine transporter (DAT) function in the knockdown rats, an effect not observed in D2 autoreceptor knockout mouse models. SN D2 knockdown rats exhibit a behavioral phenotype characterized by persistent enhancement of locomotor activity in a familiar open field, reduced locomotor responsiveness to high doses of cocaine and the ability to overcome haloperidol-induced immobility on the bar test. Together these results demonstrate that presynaptic D2 receptors can be depleted from specific neuronal populations and implicates nigrostriatal D2 receptors in different behavioral responses to psychotropic drugs. □